Breaking Standard Model global symmetries with the tau lepton - Jorge Portolés (SciPost Physics Proceedings)
Properties of the dynamics of the Standard Model processes such as lepton flavour preservation and lepton, or baryon, number conservation, are usually taken for granted. The only reason is that it seems that these non-gauge accidental symmetries of the Standard Model seem to be conserved in Nature with great accuracy. In addition, the coupling of lepton doublets to the electroweak gauge bosons is universal and does not depend on the flavour. The discovery of the non-zero mass of the neutrinos and, maybe, the hints coming from the B-anomalies at LHCb, point out to a different scenario. I will briefly summarize some aspects of these contingent symmetries as seen from tau lepton processes.